Analisis Fungsi Pragmatik Tindak Tutur Pertanyaan dalam Percakapan Bahasa Jepang antara Wisatawan Jepang dan Pemandu Wisata Indonesia di Candi Borobudur - Akhmad Saifudin; Bayu Aryanto; Iwan Setiya Budi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
This study discusses the questioning acts in a Japanese conversation. The problem was analyzed using Searle’s theory aboutthe locutionary force in speech acts. The data are in the form ofquestioning acts taken from the transcripst of the conversationbetween Japanese tourists and Indonesian guides in Borobudur temple area. The result shows that there are four pragmatic functions of questioning acts found in this conversation. They are 1) directivequestioning act, 2) expressive questioning act, 3) assertive questioning act, and 4) commisive questioning act.Keywords: Japanese Conversation, Directive Questioning Act,Expressive Questioning Act, Assertive Questioning Act, CommisiveQuestioning Act